ON THE PERIODS OF THE β CEPHEI STARS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
On the base of GCVS’ data the analysis of periods distributions for β Cep stars (BCEP and BCEPS) has been carried out. Identifications for all peaks on the histogram have been performed. There are some overtones and their harmonics. These are related with multiplicity ratios. In addition to GCVS classification it is proposed to extend the range of periods for short-period group (BCEPS) to (0.02 - 0.13) days instead of (0.02 - 0.04) days. We propose a new classification of these stars according to their mode identifications.